Impact of Perineuronal Net Removal in the Rat Medial Prefrontal Cortex on Parvalbumin Interneurons After Reinstatement of Cocaine Conditioned Place Preference - Gonzalez, Angela E.; Jorgensen, Emily T.; Ramos, Jonathan D.; Harkness, John H.; Aadland, Jake A.; Brown, Travis E.; Sorg, Barbara A. (Frontiers in Cellular Neuroscience, 2022)
Parvalbumin (PV)-positive cells are GABAergic fast-spiking interneurons that modulate the activity of pyramidal neurons in the medial prefrontal cortex (mPFC) and their output to brain areas associated with learning and memory. The majority of PV cells within the mPFC are surrounded by a specialized extracellular matrix structure called the perineuronal net (PNN). We have shown that removal of PNNs with the enzyme chondroitinase-ABC (Ch-ABC) in the mPFC prevents the consolidation and reconsolidation of cocaine-associated conditioned place preference (CPP) memories. Here we examined the extent to which retrieval of a CPP memory during cocaine-primed reinstatement altered the levels and function of PV neurons and their surrounding PNNs during the reconsolidation period. We further determined the extent to which PNN removal prior to reinstatement altered PV intensity levels and PV cell function. Male Sprague-Dawley rats were trained for cocaine-induced conditioned place preference (CPP) followed by extinction training, microinjection of Ch-ABC in the prelimbic PFC, and cocaine-induced reinstatement. Rats were sacrificed immediately prior to reinstatement or at 2 h, 6 h, or 48 h after reinstatement for immunohistochemistry or 2 h later for electrophysiology. Our findings indicate that PNN removal only partially diminished reinstatement. Cocaine-primed reinstatement produced only minor changes in PNN or PV intensity in vehicle controls. However, after PNN removal, the intensity of remaining PNN-surrounded PV cells was decreased at all times except at 2 h post-reinstatement, at which time cocaine increased PV intensity. Consistent with this, in vehicle controls, PV neurons naturally devoid of PNNs showed a similar pattern to Ch-ABC-treated rats prior to and after cocaine reinstatement, suggesting a protective effect of PNNs on cocaine-induced changes in PV intensity. Using whole-cell patch-clamp, cocaine-primed reinstatement in Ch-ABC-treated rats decreased the number of elicited action potentials but increased excitatory synaptic transmission, which may have been compensatory. These findings suggest that without PNNs, cocaine-induced reinstatement produces rapid changes in PV intensity and PV cell excitability, which may in turn regulate output of the mPFC post-memory retrieval and diminish the maintenance of cocaine memory during reconsolidation.